Proceedings of the 34th International Cosmic Ray Conference — PoS(ICRC2015) 2016
DOI: 10.22323/1.236.0867
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-ray halo around the M31 galaxy as seen by the Fermi LAT

Abstract: Theories of galaxy formation predict the existence of extended gas halo around spiral galaxies. If there are 10-100 nG magnetic fields at several ten kpc distances from the galaxies, extended galactic cosmic ray (CR) haloes could also exist. Galactic CRs can interact with the tenuous hot halo gas to produce observable gamma-rays. We have performed search for a gamma-ray halo around the M31 galaxy -the closest large spiral galaxy. Our analysis of almost 7 years of the Fermi LAT data revealed the presence of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Evidence of a spherical γ-ray halo around M31 with a 0.9 • extension is reported in Pshirkov et al (2016a). In Pshirkov et al (2016b) the morphology of the extended γ-ray emission is reported to consists of two bubbles symmetrically located perpendicular to the M31 disk, akin to the MW Fermi bubbles.…”
Section: B4 the Inner Galaxymentioning
confidence: 93%
See 2 more Smart Citations
“…Evidence of a spherical γ-ray halo around M31 with a 0.9 • extension is reported in Pshirkov et al (2016a). In Pshirkov et al (2016b) the morphology of the extended γ-ray emission is reported to consists of two bubbles symmetrically located perpendicular to the M31 disk, akin to the MW Fermi bubbles.…”
Section: B4 the Inner Galaxymentioning
confidence: 93%
“…In general, disk galaxies like M31 may be surrounded by extended CR halos (Feldmann et al 2013;Pshirkov et al 2016a). Depending on the strength of the magnetic fields in the outer galaxy, the CR halo may extend as far as a few hundred kpc from the galactic disk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following its the initial detection [2], M 31 has appeared in both the 2FGL catalogue (J0042.5+4114 [3]) and the 3FGL catalogue (J0042.5+4117 [4]), in both cases as a point source. Analyses have also been published in [14] where they examine dark matter limits from M 31 and in [15] where evidence for γ-ray emission from a spatially extended halo around M 31 is presented. We have conducted an updated analysis of the Fermi-LAT data, using the LATAnalysisScripts and Fermi Science Tools v9r33p0 to conduct a binned (0.1 • ) analysis.…”
Section: Updated Fermi-lat Analysismentioning
confidence: 99%
“…The nature and origin of the emission from the central regions of M31 remain somewhat controversial: on the one hand, M31's observed gamma-ray luminosity does not significantly deviate from the expectation from the known scaling relationship between infrared and gamma-ray luminosity ported emission extends out to roughly 100-200 kpc above the plane of the galaxy, although the authors acknowledge that the emission from the "far outer halo" (at angles from M31's center 8.5 • < r < 21 • ) is likely related to mis-modeling of the significant foreground emission from the Milky Way and thus less robust than the emission from the "Spherical Halo" region at angles between 0.4 • < r < 8.5 • and than the robustly-detected inner galaxy emission at r < 0.4 • . Karwin et al (2019), while not ruling it out, argues against an extended cosmic-ray halo (Feldmann et al 2013a;Pshirkov et al 2016b) based on the radial extent, spectral shape, and intensity of the observed large-radii signal. However, as we argue below, the radial extent and intensity depend critically on assumptions on cosmic-ray diffusion outside the Galactic plane and in the halo; and the spectral shape is strongly affected by foreground Galactic emission and from the intrinsic weakness and limited statistics of the signal.…”
Section: Introductionmentioning
confidence: 96%